Characteristics of Soft Semitrees: Enhancing the Soft Semigraph Framework - George, Bobin; Thumbakara, Rajesh K.; George, Sijo P.; Jose, Jinta (Communications in Mathematics and Applications, 2024)
Molodtsov pioneered the concept of soft sets, offering a method to classify elements of a universe based on a specified set of parameters. This approach serves to model vagueness and uncertainty. Semigraphs are a generalised form of graphs introduced by Sampathkumar et al. (Semigraphs and Their Applications, Academy of Discrete Mathematics and Applications, Mysore, India, 337 pages (2019)). Integrating soft set theory into semigraphs led to the creation of soft semigraphs. Due to its adeptness in handling parameterisation, the field of soft semigraph theory is rapidly evolving. In this study, we introduce the concept of soft semitrees and explore some of their characteristics.